2022
DOI: 10.1108/jtf-01-2022-0034
|View full text |Cite
|
Sign up to set email alerts
|

The effect of social networks on the development of gastronomy – the way forward to the development of gastronomy tourism in Serbia

Abstract: PurposeTo evaluate some of the current discussions about the possible impacts of social networks on the development of gastronomy in the Republic of Serbia. There could be either positive and/or negative impacts and this viewpoint provides some reflection on what the future might hold for some if not many tourism destinations in Serbia and the region when the tourism industry restarts after the pandemic of Covid-19 virus.Design/methodology/approachThe research was conducted in December 2021, on a total of 244 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…According to Schultz (2015) [70], today's visitors are searching for authentic travel and culinary experiences, owing in part to the role of the media, which has positively changed travelers' perspectives on the link between tourism and cuisine [71]. Several studies have shown that social networks may make a significant contribution to the promotion of cuisine and gourmet tourism [72]. In addition, it is important to point out that many previous studies have proven that gastronomic tourism can be an opportunity to socialize with other people, informally at gastronomic festivals and similar events, which all contribute to the tourist experience being even more complete [71,73,74].…”
Section: Motivation Of Gastronomic Tourists-impact On Agritourismmentioning
confidence: 99%
“…According to Schultz (2015) [70], today's visitors are searching for authentic travel and culinary experiences, owing in part to the role of the media, which has positively changed travelers' perspectives on the link between tourism and cuisine [71]. Several studies have shown that social networks may make a significant contribution to the promotion of cuisine and gourmet tourism [72]. In addition, it is important to point out that many previous studies have proven that gastronomic tourism can be an opportunity to socialize with other people, informally at gastronomic festivals and similar events, which all contribute to the tourist experience being even more complete [71,73,74].…”
Section: Motivation Of Gastronomic Tourists-impact On Agritourismmentioning
confidence: 99%
“…In addition, prospective travelers believe that they require information to make the best travel decisions (Yadav et al, 2023), and according to (Akdim, 2021), Due to the perception of other travelers as more trustworthy than other sources of information and the creation of more realistic expectations, visitors prefer to depend on internet reviews for unbiased information. This is also tied to the development of tourists utilizing social media so that they can write reviews based on their personal experiences (Vukolic et al, 2022), which other travelers can use as a reference.…”
Section: Online Reviewmentioning
confidence: 99%
“…LinkedIn, Facebook, Twitter, Instagram and other applications provide new patterns of communication in social interaction [42]. Social networks include computer-mediated technology that enable the growth and exchange of awareness, ideas, interests, information and other methods of expression through virtual communities [36] [50]. Social media users can see or read online posts posted by their friends without directly interacting with them [30].…”
Section: Literature Reviewmentioning
confidence: 99%